ECONOMIC AND SOCIAL LIFE IN SİVAS AND IN THE NEIGHBOURHOOD AT THE END OF THE 19TH CENTURY ACCORDING TO THE REPORTS BY SİVAS CONSULATE OF UNITED STATES OF AMERICA (1887-1893) - Osman Kubilay GÜL (International Journal of Eurasia Social Sciences, 2015)
Through the end of the 19th century, The Ottoman Empire was having troubles in almost every aspect. Especially, the deterioration in the administrative and economic system had severe and adverse effects on the people living in Anadolu. In such a period, missionaries were working actively in all parts of Anadolu and Foreign States were opening up new consulates. In 1886, American Consulate in Sivas was established so as to make things easierr for the missionaries working in Sivas and to benefit from the trade in the region. The consulate was active between the years 1886-1906, and especially during the fisrt five years the consulate prepared important reports about the economic and social life in Sivas. These reports gathered many information on various topics such as trade, agriculture, husbandry, clothing, working-life, mineral deposit and transportation. Outsider consulates who came to examine Sivas inform us about the administrative structure in Ottoman Empire, life-styles of the poeple in Sivas and the social life